2016
DOI: 10.1016/j.jpsychires.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessment versus standard assessment instruments for measuring mindfulness, depressed mood, and anxiety among older adults

Abstract: As mobile data capture tools for patient-reported outcomes proliferate in clinical research, a key dimension of measure performance is sensitivity to change. This study compared performance of patient-reported measures of mindfulness, depression, and anxiety symptoms using traditional paper-and-pencil forms versus real-time, ambulatory measurement of symptoms via ecological momentary assessment (EMA). Sixty-seven emotionally distressed older adults completed paper-and-pencil measures of mindfulness, depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
144
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(153 citation statements)
references
References 31 publications
6
144
1
2
Order By: Relevance
“…Second, this study relied on self-reported measures of time spent engaging in home practice of MBSR techniques. Technological advancements, such as ecological momentary assessment, 35 could enable future investigations to track use of these techniques more carefully. Third, although the 60-item Revised NEO Personality Inventory has consistently been found reliable and valid across contexts and cultures, 18 the current study examined only the five broad personality domains.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study relied on self-reported measures of time spent engaging in home practice of MBSR techniques. Technological advancements, such as ecological momentary assessment, 35 could enable future investigations to track use of these techniques more carefully. Third, although the 60-item Revised NEO Personality Inventory has consistently been found reliable and valid across contexts and cultures, 18 the current study examined only the five broad personality domains.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety questions were included because participants were selected for this study based on meeting criteria for depression or an anxiety disorder. Depression and anxiety were measured with National Institutes of Health (NIH) Patient Reported Outcomes Measurement Information System (PROMIS) short form instruments which have been validated in prior research (Cella et al, 2007, 2010; Reeve et al, 2007) and found to have excellent internal consistency when administered via EMA (Moore, Depp, Wetherell, & Lenze, 2016). Mindfulness questions were included because we believed that mindfulness—a construct that emphasizes present moment experience—was particularly well suited for EMA data collection and relevant to the proposed mechanism underlying the RCT.…”
Section: Methodsmentioning
confidence: 99%
“…Mindfulness questions were included because we believed that mindfulness—a construct that emphasizes present moment experience—was particularly well suited for EMA data collection and relevant to the proposed mechanism underlying the RCT. Mindfulness was measured using items from the Cognitive Affective Mindfulness Scale-Revised (CAMS-R) which has been validated in prior research (Feldman, Hayes, Kumar, Greeson, & Laurenceau, 2007) and found to have adequate internal consistency equivalent to that of paper-and-pencil administration (Moore et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…This standard scale can be supplemented by patient-reported outcomes, including psychological well-being. Mobile technology in clinical research is increasingly feasible and acceptable to older adults; 34 it can carry out more accurate assessments 35 or even fully mobile clinical trials, 36 but researchers need to be cognizant of security concerns and perceived burden of answering assessments. For any technology-based assessment, Computer Adaptive Testing can reduce the amount of items needed, which reduces burden on participants and potentially individualizes the measure to their specific concerns.…”
Section: Discussionmentioning
confidence: 99%